Rasa Khawatir Moralis Tokoh Utama dalam Novel Truntum Karya Siti Aminah - Rahmawati, Isnani; Darni, Darni (Jurnal Online Baradha, 2023)
ABSTRACT The psychological problem experienced by the main character in Truntum's novel is in the form of moralist worry which is studied with Sigmund Freud's theory of psychoanalysis. This worry arises when what a person does goes against the moral norms controlled by the superego. The purpose of this study is to explain the feeling to (1) explain the form of moralist worry of the main character, and (2) explain the defense mechanism of the main character's ego. These two goals will be achieved with Sigmund Freud's theory of psychoanalysis. This research was analyzed using qualitative descriptive method. The source of this research data is the novel Truntum by Siti Aminah. Research data were taken from novels in the form of words, sentences, paragraphs, and conversations related to the main character's moralist worries and ego defense mechanisms. The data in this study was collected using literature study techniques. The results of this study explain the form of the main character's worry in the form of moralist worry experienced by the main character including regret, and feeling guilty. To reduce the moralist worry of the main character, ego defense mechanisms are used with repression, rationalization, and sublimation. The rationalization that the main character does is to think of something logical to forget the worry. Keywords: Moral Worry, Superego, Rationalization ABSTRAK Problem psikologis yang dialami oleh tokoh utama dalam novel Truntum ini berupa rasa khawatir moralis yang dikaji dengan teori psikoanalisis Sigmund Freud. Rasa khawatir ini timbul ketika apa yang dilakukan seseorang bertentangan dengan norma moral yang dikendalikan oleh superego. Tujuan penelitian ini yaitu menjelaskan rasa untuk (1) menjelaskan bentuk rasa khawatir moralis tokoh utama, dan (2) menjelaskan mekanisme pertahanan ego tokoh utama. Dua tujuan tersebut akan dicapai dengan teori Psikoanalisis Sigmund Freud. Penelitian ini dianalisis menggunakan metode deskriptif kualitatif. Sumber data penelitian ini yaitu novel Truntum karya Siti Aminah. Data-data penelitian diambil dari novel yang berupa kata, kalimat, paragraf, serta percakapan yang berkaitan dengan rasa khawatir moralis tokoh utama serta mekanisme pertahanan ego. Data dalam penelitian ini dikumpulkan dengan menggunakan teknik studi pustaka. Hasil penelitian ini menjelaskan bentuk rasa khawatir tokoh utama yang berupa rasa khawatir moralis yang dialami tokoh utama meliputi rasa menyesal, dan merasa bersalah. Untuk mengurangi rasa khawatir moralis tokoh utama maka mekanisme pertahanan ego yang digunakan dengan represi, rasionalisasi, dan sublimasi. Rasionalisasi yang dilakukan tokoh utama yaitu dengan memikirkan sesuatu yang logis untuk melupakan rasa khawatir. Kata Kunci: Rasa Khawatir Moralis, Superego, Rasionalisasi